Frederick T. Frelinghuysen papers - Frelinghuysen, Frederick T. (Frederick Theodore), 1817-1885.
Drafts of diplomatic letters and memoranda sent to American consuls, ministers, and other agents abroad, and to government officials in the U.S., many signed by John R. Davis, relating to the surrender of international criminals, collection of claims, commercial practices, and reciprocity negotiations chiefly with Latin American countries and Spanish colonies in the West Indies, boundary disputes in Mexico, Guatemala, Chile, Peru, and Colombia, and the lease of the naval base at Pearl Harbor.
Lawyer, U.S. secretary of state, and U.S. senator from New Jersey.
Collection material in English.
Keywords: Davis, John R; Navy-yards and naval stations -- Hawaii -- Pearl Harbor; Chile -- Boundaries; Colombia -- Boundaries; Guatemala -- Boundaries; Latin America -- Foreign relations -- United States; Mexico -- Boundaries; Peru -- Boundaries; Spain -- Colonies -- America; United States -- Foreign relations -- Latin America; West Indies -- History; Cabinet officers; Lawyers; Senators, U.S. Congress -- New Jersey